The Effect of Maltodextrin Supplementation on Anaerobic Power of Rowing Athletes - Anggi Widiarti; Dede Rohmat Nurjaya; Angga M Syahid (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Maltodextrin, a high-glycemic carbohydrate, is believed to maintain energy and delay muscle fatigue in rowing, a sport that relies on both aerobic and anaerobic energy sys-tems. The purpose of this study was to evaluate the effectiveness of maltodextrin supplementation in maintaining energy and anaerobic performance in rowing athletes. The research with a randomized pretest–posttest control group design involved eight rowing athletes from West Bandung Regency, divided into an experimental group (receiving 0.25 g/kg maltodextrin) and a control group (water). The main instrument used is the Concept-2 rowing ergometer which is equipped with a digital monitor to record power output, stroke rate, and mileage for each sprint. Data were analyzed descriptively to see the mean and difference between groups, followed by the Shapiro–Wilk normality test and the Levene homogeneity test. The results showed that maltodextrin supplementation did not have a statistically significant effect on the increase in anaerobic power of rowing athletes, but physiologically had a positive ef-fect on performance. The group that received maltodextrin had a lower fatigue index (13.5%) than the control group (17.6%), indicating a better ability to maintain strength during repeated sprints. Conclusion This study showed that maltodextrin supplemen-tation at a dose of 0.25 g/kg body weight given two hours before activity had a practi-cal positive effect on the anaerobic power of rowing athletes in West Bandung Re-gency.